KETIDAKSETARAAN GENDER DI TEMPAT KERJA : TINJAUAN MENGENAI PROSES DAN PRAKTEK DALAM ORGANISASI - Leovani, Ega; Ismadi, Florentinus Heru; Terenggana, Candra Astra (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2023)
This article aims to examine more broadly the extent of gender inequality in processes and practices covering a wide range of areas ranging from performance evaluation, compensation, and leadership opportunities, to sexual harassment in organizations. This literature review makes it possible to review the factors that facilitate and hinder gender equality in the workplace. The review identifies gaps in the literature review provides suggestions for future research and highlights practical implications for organizations aiming to reduce gender inequality and value gender equality in organizations.